PENJABARAN GOOD CORPORATE GOVERNANCE (GCG) DALAM PENGADAN BARANG DAN JASA PADA PLN BALI - Luh Putu Dwi Suarini (University of Udayana, 2015)
Research in connection with the theme is “ Implementation of Good Corporate Governance(GCG) in Procurement at PLN Bali”. The problems are researched the translation of goodcorporate governace forms in the procurement of goods and services at PLN Bali and theform of the procurement of goods and services at PLN Bali.This research includes the category of empirical legal research, legal research is a empiricalmeans reviewing the practical reality in daily life - today. The nature of the research isdescriptive research that has a goal to paint a picture of something in the area and at acertain moment. Furthermore, the technique used is to study documents, interviews, Non-Probability Sampling, purposive sampling.Procurement of goods or services in PLN involves many parties, the employees who wereappointed to take care of such procurement and future providers of goods and services.In this relationship unfair business competition or the price is too high or low in supply.However, the existence of e-procurement and the correct procedures in the procurementof goods and services as well as the concept of GCG which also animates the principles ofprocurement of goods and services. Procedures in the procurement of goods and servicesas well as the principles of GCG, the procurement in PLN can be carried out transparently,responsibly, independently, fairly and equitably.